Cellular and molecular characterization of a stem rust resistance locus on wheat chromosome 7AL. (December 2016) - Pujol, Vincent; Robles, Jose; Wang, Penghao; Taylor, Jen; Zhang, Peng; Huang, Li; Tabe, Linda; Lagudah, Evans
Abstract Background Wheat stem rust, caused byPuccinia graminis f. sp.tritici, is a major wheat disease which is mainly controlled through the release of resistant cultivars containing one or several resistance genes. Considerable effort has been put into the discovery of new resistance genes, but knowledge of their mechanisms of action is often lacking. In this study, the mechanism of resistance conferred by a recently discovered stem rust resistance locus on wheat chromosome 7AL was investigated through microscopic observations and RNA-sequencing, using the susceptible line Columbus and the independent, backcrossed, resistant lines Columbus-NS765 and Columbus-NS766. Results Microscopic observations of infected leaves revealed that the resistance conferred by the 7AL resistance locus was initiated 2 days post-inoculation, upon the fungus entry into the plant through the stoma. Resistance was manifested by death of guard and epidermal cells adjacent to an infection site. Occasionally, similar observations were made in the susceptible line, suggesting that the resistance response was the same in all genotypes, but enhanced in the resistant lines. Transcriptomic analysis, combined with assignment of genes to wheat chromosomes, revealed a disproportionately high number of differentially expressed genes were located on chromosomes 7AL and 6A. A number of genes annotated as cysteine-rich receptor-like kinases were located on chromosome 7AL. Closer investigation indicated that the encoded proteins were in fact putative receptor-like cytoplasmic kinases. One of the putative RLCK genes contained a SNP marker previously shown to co-segregate with the 7AL resistance locus. The results also indicated the presence of a large introgression on chromosome 6A in both resistant lines, but whether it has any role in the resistance response is unclear. Conclusions This study represents the first investigation on the resistance mechanism conferred by the wheat 7AL stem rust resistance locus. The resistance response was associated with pre-haustorial cell death, and the transcriptome analysis suggested putative receptor-like cytoplasmic kinases as candidate resistance genes for further investigation.